(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the role of artistic detail in the creation of female characters in modern Uzbek prose. The study highlights the importance of artistic detail in revealing the inner state and psychological experiences of the character. It examines how the individual features of female characters are expressed through detail. The aesthetic function of artistic detail in character construction is also determined.